Exact powers of some multivariate test criteria - Hart, Michael Lester (Department of Statistical Sciences, 2016)
In this thesis an algorithm for the noncentral linear density and cumulative distribution function of Wilks' likelihood ratio criterion in MANOVA is derived and it is shown how this algorithm, with modifications, can be used to find the distributions of a number of test criteria for different hypotheses. At the same time previous results regarding percentiles and powers of these criteria are examined and discussed.